2020
DOI: 10.1200/jco.2020.38.15_suppl.4502
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative trastuzumab and pertuzumab in combination with FLOT versus FLOT alone for HER2-positive resectable esophagogastric adenocarcinoma: Final results of the PETRARCA multicenter randomized phase II trial of the AIO.

Abstract: 4502 Background: Perioperative FLOT is a standard of care for resectable, esophagogastric adenocarcinoma (EGA). This trial evaluates the addition of trastuzumab (tras) and pertuzumab (per) to FLOT for HER2-positive resectable patients (pts). Methods: PETRARCA is a prospective, multicenter, randomized, investigator initiated trial planned as a phase II/III investigation. We report the phase II part of this trial. Pts with HER2+ resectable EGA (≥ cT2 or cN+) were enrolled. Pts were randomized 1:1 to 4 pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 0 publications
1
59
0
2
Order By: Relevance
“…PETRARCA trial showed that the addition of both Trastuzumab and Pertuzumab to FLOT in perioperatively significantly improved the compete pathological response rate (35% vs 12%) with improvement in node-negative outcome (68% vs. 39%). However, due to increased toxicities when adding both HER2 agents including grade3/4 diarrhea (41% vs 5%) and leukopenia (23% vs. 13%), this study is not being moved to the phase III [46].…”
Section: Cytotoxic Therapiesmentioning
confidence: 99%
“…PETRARCA trial showed that the addition of both Trastuzumab and Pertuzumab to FLOT in perioperatively significantly improved the compete pathological response rate (35% vs 12%) with improvement in node-negative outcome (68% vs. 39%). However, due to increased toxicities when adding both HER2 agents including grade3/4 diarrhea (41% vs 5%) and leukopenia (23% vs. 13%), this study is not being moved to the phase III [46].…”
Section: Cytotoxic Therapiesmentioning
confidence: 99%
“…Based on these post hoc subgroup analyses, trastuzumab was approved in many countries in addition to the cisplatin-fluoropyrimidine doublet, representing the standard of care in the first-line treatment for patients with HER2-positive disease [2]. Additionally, several trials are currently investigating the efficacy of anti HER2 agents in the adjuvant and neoadjuvant settings for HER2 positive GC [12][13][14][15]; one of them, i.e., the PETRARCA study, has suggested improved pathological complete response rates for neoadjuvant chemotherapy and HER2 directed therapy [15].…”
Section: Human Epidermal Growth Factor Receptor 2: the First Step In mentioning
confidence: 99%
“…An example of a study in the curative setting is the PERTRARCA study by the FLOT-AIO group, of which the results were recently presented at the ASCO annual meeting (78). Patients with resectable HER-2 positive esophagogastric carcinoma were randomized between four perioperative cycles of FLOT with or without trastuzumab, followed by nine cycles of trastuzumab plus pertuzumab.…”
Section: Human Epidermal Growth Factor Receptor 2 (Her-2) Overexpressmentioning
confidence: 99%